Children's sugar-sweetened beverages consumption: associations with family and home-related factors, differences within ethnic groups explored. (December 2017) - van de Gaar, V.; van Grieken, A.; Jansen, W.; Raat, H.
Abstract Background The consumption of sugar-sweetened beverages (SSB) may contribute to the development of overweight among children. The present study aimed to evaluate associations between family and home-related factors and children's SSB consumption. We explored associations within ethnic background of the child. Methods Cross-sectional data from the population-based 'Water Campaign' study were used. Parents (n  = 644) of primary school children (6-13 years) completed a questionnaire on socio-demographic characteristics, family and home-related factors and child's SSB intake. The family and home-related factors under study were: cognitive variables (e.g. parental attitude, subjective norm), environmental variables (e.g. availability of SSB, parenting practices), and habitual variables (e.g. habit strength, taste preference). Regression analyses were used to evaluate the associations between family and home-related factors and child's SSB intake (p  < 0.05). Results Mean age of the children was 9.4 years (SD: 1.8) and 54.1% were girls. The child's average SSB intake was 0.9 litres (SD: 0.6) per day. Child's age, parents' subjective norm, parenting practices, and parental modelling were positively associated with the child's SSB intake. The availability of SSB at home and school and parental attitude were negatively associated with the child's SSB intake. The associations under study differed according to the child's ethnic background, with the explained variance of the full models ranging from 8.7% for children from Moroccan or Turkish ethnic background to 44.4% for children with Dutch ethnic background. Conclusions Our results provide support for interventions targeting children's SSB intake focussing on the identified family and home-related factors, with active participation of parents. Also, the relationships between these factors and the child's SSB intake differed for children with distinct ethnic backgrounds. Therefore, we would recommend to tailor interventions taking into account the ethnic background of the family. Trial registration NumberNTR3400 ; date April 4th 2012; retrospectively registered.